TINJAUAN ASPEK EPIDEMIOLOGI TERHADAP FENOMENA WISATAWAN MANCANEGARA DENGAN MASALAH GANGGUAN MENTAL - Utama, I Putu Sagita Jaya; Tri Oktin Windha Daniaty (UHN IGB Sugriwa Denpasar, 2024)
Travelers traveling cross-country are at risk of exposure to many unforeseen medical problems. According to the World Health Organization, mental disorders are one of the three main health complications associated with air travel. Of all mental disorders encountered on international travel, acute psychotic episodes account for about one fifth. Stressful conditions during traveling, such as feeling lonely, feeling out of control, financial difficulties, traumatic events (accidents, abuse, becoming victims of crime) and the environment (natural disasters) can cause behavioral and psychosocial consequences for tourists. So, the contribution to the review from the epidemiological aspect by utilizing the results of observations and analyzing some of the literature and literature that is relevant to the object of research, is the aim of writing this article.